Genome In Silico and In Vitro Analysis of the Probiotic Properties of a Bacterial Endophyte, Bacillus Paranthracis Strain MHSD3 - Diale, Mamonokane Olga; Kayitesi, Eugenie; Serepa-Dlamini, Mahloro Hope (Frontiers in Genetics, 2021)
Spore-forming Bacillus species are gaining interest in human health recently, due to their ability to withstand the harsh environment of the gastrointestinal tract. The present study explores probiotic features of Bacillus paranthracis strain MHSD3 through genomic analysis and in vitro probiotic assays. The draft genome of strain MHSD3 contained genes associated with tolerance to gastrointestinal stress and adhesion. Cluster genes responsible for the synthesis of antimicrobial non-ribosomal peptide synthetases, bacteriocins, and linear azole-containing peptides were identified. Additionally, strain MHSD3 was able to survive in an acidic environment, had the tolerance to bile salt, and exhibited the capability to tolerate gastric juices. Moreover, the isolate was found to possess strong cell surface traits such as high auto-aggregation and hydrophobicity indices of 79 and 54%, respectively. Gas chromatography–mass spectrometry analysis showed that the strain produced secondary metabolites such as amino acids, phenolic compounds, and organic acid, known to exert health-promoting properties, including the improvement of gastrointestinal tract health.